A hominoid-specific endogenous retrovirus may have rewired the gene regulatory network shared between primordial germ cells and naïve pluripotent cells - Ito, Jumpei; Seita, Yasunari; Kojima, Shohei; Parrish, Nicholas F.; Sasaki, Kotaro; Sato, Kei (PLoS genetics, 2022)
Mammalian germ cells stem from primordial germ cells (PGCs). Although the gene regulatory network controlling the development of germ cells such as PGCs is critical for ensuring gamete integrity, substantial differences exist in this network among mammalian species, suggesting that this network has been modified during mammalian evolution. Here, we show that a hominoid-specific group of endogenous retroviruses, LTR5_Hs, discloses enhancer-like signatures in human in vitro -induced PGCs, PGC-like cells (PGCLCs). Human PGCLCs exhibit a transcriptome signature similar to that of naïve-state pluripotent cells. LTR5_Hs are epigenetically activated in both PGCLCs and naïve pluripotent cells, and the expression of genes in the vicinity of LTR5_Hs is coordinately upregulated in these cell types, contributing to the establishment of the transcriptome similarity between these cell types. LTR5_Hs are preferentially bound by transcription factors that are highly expressed in both PGCLCs and naïve pluripotent cells ( KLF4 , TFAP2C , NANOG , and CBFA2T2 ), suggesting that these transcription factors contribute to the epigenetic activation of LTR5_Hs in these cells. Comparative transcriptome analysis between humans and macaques suggests that the expression of many genes in PGCLCs and naïve pluripotent cells is upregulated by LTR5_Hs insertions in the hominoid lineage. Together, this study suggests that LTR5_Hs insertions may have finetuned the gene regulatory network shared between PGCLCs and naïve pluripotent cells and coordinately altered the gene expression in these cells during hominoid evolution.